In vitro reactivation of tabun-inhibited acetylcholinesterase using new oximes--K027, K005, K033 and K048 - Kuca, K; Cabal, J (Central European journal of public health, 2004)
Four new AChE oximes for reactivation of acetylcholinesterase inhibited with tabun - K027 [1-(4-hydroxyiminomethylpyridinium)-3-(4-carbamoylpyridinium) propane dibromide], K005 [1,3-bis(2-hydroxyiminomethylpyridinium) propane dibromide], K033 [1,4-bis(2-hydroxyiminomethylpyridinium) butane dibromide] and K048 [1-(4-hydroxyiminomethylpyridinium)-4-(4-carbamoylpyridinium) butane dibromide] were prepared. Their efficacies to reactivate tabun-inhibited acetylcholinesterase were studied and compared with the currently used acetylcholinesterase reactivators (pralidoxime, obidoxime and HI-6). Reactivator K048 seems to be promising reactivator of tabun-inhibited AChE. Its reactivation potency is significantly higher than the efficacy of HI-6 and pralidoxime, and comparable with the potency of the obidoxime at human relevant doses.
Keywords: Cholinesterase Reactivators; reaktivátory cholinesterasy; mozek; Pyridinium Compounds; oximy; krysa rodu Rattus; techniky in vitro; Cholinesterase Inhibitors; Organophosphates; organofosfáty; Animals; pyridinové sloučeniny; Oximes; cholinesterasové inhibitory; zvířata; In Vitro Techniques; Brain; Rats